Combination therapy with oral ursodeoxycholic and chenodeoxycholic acids: pretreatment computed tomography of the gall bladder improves gall stone dissolution efficacy. Issue 3 (March 1992) - Walters, J R; Hood, K A; Gleeson, D; Ellul, J P; Keightley, A; Murphy, G M; Dowling, R H
Abstract : In a five year study, 55 patients with radiolucent gall stones were treated with the combination of 7.5 mg chenodeoxycholic acid (CDCA) and 5.0 mg ursodeoxycholic acid (UDCA)/kg/day--that is, half the monotherapeutic doses. Side effects were few but four patients could not tolerate the prescribed bile acids because of diarrhoea or nausea. Analysis of fasting duodenal bile confirmed that CDCA+UDCA converted supersaturated into unsaturated bile but the saturation indices did not predict the dissolution response. By actuarial analysis, the confirmed (by ultrasound x2) complete gall stone dissolution rates in all 55 patients were mean (SEM) 29 (7)% at 12 and 44 (8)% at 24 months. The advent of routine computed tomography before treatment enabled comparison of dissolution efficacy in those screened by computed tomography (n = 24), whose maximum gall stone attenuation was less than 100 Hounsfield units, with that in those not screened (n = 29). Although stone size and number were comparable, patients screened by computed tomography had significantly better dissolution rates (p less than 0.025) than those not screened in this way. At 12 months, partial or complete gall stone dissolution rates were 93 (7)% in the screened and 55 (11)% in the non-screened patients. At 18 months, complete dissolution rates were 64 (12%) and 20 (9)% respectively. Computed tomography before treatment is cost effective in selecting those patients likely to achieve gall stone dissolution on treatment with UDCA+CDCA.